Host Plant Preferences, Ecological Factor And Molecular Phylogeny Of Tetraponera rufonigra JERDON (Hymenoptera: Formicidae) In Eastern Part Of Penang Island, Malaysia - Sabtu, Faezah Syukriah (2018)
Tetraponera rufonigra, commonly known as the arboreal bicolored ant has gained its notoriety as one of the medically-important pest insects in Malaysia. Tetraponera rufonigra is recognizable by its excruciating sting, causing a severe anaphylaxis especially to those with the history of allergy. A study was conducted to survey preferable trees infested by T. rufonigra across urban areas in Eastern part of Penang Island by collecting samples at sites with different types of trashes on surrounding the perimeter of trees. The survey was carried out in 11 sub-districts i.e. Bayan Lepas, Pulau Tikus, Air Itam, Jelutong, Georgetown, Gelugor, Sungai Nibong, Bayang Baru, Batu Maung, Teluk Kumbar and Sungai Ara.